Vocabulary teaching in Malaysian primary schools: a study on teacher strategies and practices - Mohd Tahir, Siti Nur Badriah; Mohd Ramli, Nor Fazlin; Manap, Mohd Radzi (Universiti Teknologi MARA, 2025)
Vocabulary instruction plays a crucial role in English language learning, yet there is limited research on how Malaysian ESL primary school teachers approach vocabulary teaching. This study examines the vocabulary learning strategies (VLS) used by Malaysian teachers, focusing on survey-based quantitative data. A total of 134 ESL primary school teachers participated in a structured survey assessing the frequency of different VLS based on Schmitt’s (1997) taxonomy. Findings indicate that social and memory strategies are the most commonly used, while metacognitive strategies are the least adopted. The results highlight the need for targeted professional development to equip teachers with diverse, effective vocabulary instruction methods.